Diffusive leakage of brine from aquifers during CO2 geological storage. (January 2018) - Dejam, Morteza; Hassanzadeh, Hassan
Highlights: Diffusive leakage of brine from aquifers during CO2 geological storage is analyzed. New type curves for average aquifer and overburden pressures are generated. Leakage rate is scaled with t 1/2 at early times and remains constant at late times. Average aquifer pressure is scaled with t for short and long times. Average overburden pressure is scaled with t at late times and with t 3/2 at early times. Case studies for two potential sites in United Kingdom are conducted to evaluate model. Abstract: The area of investigation in this study is designed around an improved understanding of fundamentals of the diffusive leakage of brine from a storage aquifer into overlying and underlying low permeability layers during geosequestration of carbon dioxide (CO2 ) through development of a theoretical model. Here, we consider a two-dimensional domain in cylindrical coordinates, comprised of an aquifer and an overburden, where the interaction between the two media is handled by imposing the continuities of pressures and fluid fluxes at the aquifer-overburden interface. This coupled problem is solved by successive implementation of the Laplace and finite Hankel transforms. The developed solutions can be used to analyze diffusive leakage of brine from the aquifer into overburden and generate type curves for average pressures in the aquifer and overburden during injection and post injection periods. The results show that the leakage rate at early times is scaled with t 1/2 while it remains constant at late times. It is also shown that the average pressure in the aquifer is scaled with t for short and long times. Moreover, the average pressure in the overburden is scaled with t at late times while it is scaled with t 3/2 at early times. In addition, the results reveal that factors affecting diffusive leakage rate through intact overburden during CO2 storage are, in decreasing order of significance, thickness of overburden, thickness of aquifer, aquifer to overburden permeability ratio, and aquifer to overburden porosity ratio. However, thickness of aquifer has minimal effect on diffusive leakage of brine within post injection period. To evaluate the theoretical model, case studies for two potential sites in United Kingdom, one in Lincolnshire and the other one in the Firth of Forth, are conducted. The field studies show that the diffusive leakage from the aquifer into the overburden diminishes ∼40 years after the injection has ceased for Lincolnshire while it stops after ∼12 years for Firth of Forth. The average amount of the brine leaked from the aquifers per standard cubic meter (Sm 3 ) of the injected CO2 through diffusive leakage was found to be 6.28 × 10 −4 m 3 of brine (or 0.330 kg of brine/kg of CO2 ) over ∼70 years for Lincolnshire and 4.59 × 10 −4 m 3 of brine (or 0.242 kg of brine/kg of CO2 ) over ∼42 years for Firth of Forth. Graphical abstract: Image, graphical abstract